Three Dimensional Brain Reconstruction Optimizes Surgical Approaches and Medical Education in Minimally Invasive Neurosurgery for Refractory Epilepsy - Swaminathan, Arun (Frontiers in Surgery, 2021)
Epilepsy is a prevalent condition that affects 1-3% of the population or about 50-65 million people worldwide (WHO estimates) and about 3.5 million people in the USA alone (CDC estimates). Refractory epilepsy refers to patients that respond inadequately to medical management alone (at least two anti-seizure medications at appropriate doses) and are appropriate candidates for other interventions such as brain surgery or the use of neurostimulators for their epilepsy. Minimally invasive techniques like stereotactic EEG electrodes offer excellent investigational abilities to study the diagnostic attributes of the seizure networks, while therapies like laser ablations and neurostimulators permit intervention and modulation of these networks to offer seizure control with minimal cognitive compromise and surgical morbidity. The accuracy of these techniques is highly contingent on precise anatomical correlation between the location of the electrodes and their proximity to relevant structures of the brain. Ensuring good anatomical correlation using 3-dimensional reconstructions would permit precise localization and accurate understanding of the seizure networks. Accurate localization of stereotactic electrodes would enable precise understanding of the electrical networks and identify vital nodes in the seizure network. These reconstructions would also permit better understanding of the proximity of these electrodes to each other and help confirm arrangement of neurostimulators to maximize modulatory effects on the networks. Such reconstructions would enable better understanding of neuroanatomy and connectivity to improve knowledge of brain structures and relations in neurological conditions. These methods would enable medical students and doctors-in-training to better their understanding of neurological disease and the necessary interventions.